Prosedur Fuzzy Tahani Menggunakan Fungsi Representatif Kurva Segitiga dan Trapesium - Wise Ahmad Sofia; Juhari Juhari (Mathematics Department, Maulana Malik Ibrahim State Islamic University of Malang, 2021)
Fuzzy Tahani is one of the developments of fuzzy logic applications. This study will explain the fuzzy Tahani procedure using representative membership functions of triangular and trapezoidal curves with fuzzification steps, determining fuzzy domains, membership functions and degrees, compiling criteria, determining fire strength values, and determining recommendation results. The fuzzy Tahani method uses the AND operation so as to produce a minimum fire strength value that affects the recommendation results. Then the research variables used are price, dimensions, weight, battery capacity, and screen display variables. For the triangular curve there are 3 fuzzy sets, namely small, medium, and large, while the trapezoidal curve consists of 4 fuzzy sets, namely small, medium, large, and very large. The data used in this study is secondary smartphone data, branded Oppo, Xiaomi, Samsung, Vivo, and Asus. From the results of smartphone data analysis according to the Fuzzy Tahani method used, these variables are processed by entering the rules, amounting to 243 for triangular curves and 1,024 for trapezoidal curves and then processed using AND operation and the conclusion is that triangular curves are better than trapezoidal curves. in recommending the purchase of a smartphone